THE INFLATION IMPACT ON THE ECONOMIC DEVELOPMENT OF SOCIETY - Vlasiuk, V. Ye. (Science and Transport Progress, 2008)
The article is devoted to theoretical-methodical problems of the study of factors of influencing the inflation processes on the economic development of society. The author has analyzed the state counter-measures to neutralize the negative effects of inflation.